PySUNDIALS : Providing python bindings to a robust suite of mathematical tools for computational systems biology - Dominy, James Gilmour (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2009.